2009
DOI: 10.1093/eurjhf/hfp043
|View full text |Cite
|
Sign up to set email alerts
|

Plasma apelin concentration is depressed following acute myocardial infarction in man

Abstract: AimsApelin, a novel peptide with a putative role in cardiovascular homeostasis, has gained interest as an endogenous inotrope, but has yet to be described following acute myocardial infarction (AMI) in man. We aimed to characterize plasma apelin concentrations following AMI and to examine its relationship with clinical and prognostic biomarkers. Methods and resultsPlasma concentrations of apelin, N-terminal probrain natriuretic peptide (NT-proBNP), norepinephrine, and arginine vasopressin were measured in 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 30 publications
(53 reference statements)
2
47
0
1
Order By: Relevance
“…This finding was confirmed in other studies conducted among subjects with stable angina (SA), and the plasma apelin levels were found to be negatively correlated with the severity of the disease [160] . A decrease of Apelin levels early after AMI has also been reported, with a progressive elevation over time, however reaching values lower than control subjects at 24 wk [161] . These observation were confirmed in patients with a first STEMI, where the reduction in apelin levels was independent from left ventricular dysfunction and outcome [162] .…”
Section: Apelinmentioning
confidence: 80%
“…This finding was confirmed in other studies conducted among subjects with stable angina (SA), and the plasma apelin levels were found to be negatively correlated with the severity of the disease [160] . A decrease of Apelin levels early after AMI has also been reported, with a progressive elevation over time, however reaching values lower than control subjects at 24 wk [161] . These observation were confirmed in patients with a first STEMI, where the reduction in apelin levels was independent from left ventricular dysfunction and outcome [162] .…”
Section: Apelinmentioning
confidence: 80%
“…37 Relevant studies conducted so far have shown that apelin plays a role in regulation of blood pressures, cardiac contractility, fluid balance, anterior pituitary functions, angiogenesis and inhibition of apoptosis. 38,39 Due to abovementioned effects of the apelinergic system, it can be assumed that apelin affects volume regulation, blood pressure and the cardiovascular system in PD patients. However, this is the first study to investigate the relation between the apelinergic system and affective disorders in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of PI3/Akt or P70S6 kinase was found to produce no effect on apelin-mediated cardioprotection (Kleinz & Baxter 2008). Further evidence for apelin's role in myocardial injury was provided by a report whereby plasma apelin is reduced in humans following MI and remains depressed for 24 weeks (Weir et al 2009). In animal studies, apelin knockout mice display increased cardiac dysfunction and increased myocardial remodelling in aging and in response to pressure overload, suggesting an important role for endogenous apelin in the regulation of cardiac function in response to insult (Kuba et al 2007).…”
Section: Apelinmentioning
confidence: 99%